Intersectoral Cooperation for Sustainability: Implementing the Whole-School Approach as a National Certification Model for Promoting Physical Activity in Polish Schools (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This project aims to strengthen whole-school physical activity (PA) promotion in Poland by developing and implementing a national school-certification framework. It addresses multiple public health challenges and supports SDG17 – Partnerships for a More Active World. The initiative targets primary and secondary schools and is inspired by the WHO’s Promoting Physical Activity Through Schools: A Toolkit. The framework supports schools in adopting a self-tailored, systems-based approach to embedding PA into daily routines, school culture, and the environment. A key innovation lies in the assumption that every school possesses the potential for PA development, and in the use of a ‘comply or explain’ methodology that encourages schools to critically assess and design their development.Project Description: The project was developed under the nationwide ‘WF z AWF’ (PE with the University of Physical Education) multisectoral participatory initiative, involving interdisciplinary experts, school representatives, and governmental stakeholders.Development: The framework, aligned with the WHO Toolkit, was co-created with input from educators, health professionals, policymakers, parents, and school leaders. Its evaluation criteria reflect WHO action areas such as quality PE, active travel, leadership, school culture, inclusion, and community engagement.Implementation: Schools participate voluntarily, documenting existing PA efforts and planning future improvements. They use digital self-assessment tools and attend support workshops. A national database of best practices enables peer learning and inspires scalable, systemic change. Over 100 schools are expected to join the first phase.Evaluation: Ongoing quantitative and qualitative measures of effectiveness include school readiness, implementation progress, and stakeholder feedback. The framework is currently being scaled, with plans for long-term monitoring and policy integration.Dissemination: Results and exemplary practices are shared via open access platforms, professional networks, and national events to encourage wider uptake.Conclusion: This WHO-aligned certification framework provides a scalable strategy to embed health-enhancing PA in schools. By emphasising teacher-led innovation and reflective practice over externally imposed standards, it supports locally relevant change and long-term sustainability. It contributes to intersectoral collaboration, teacher development, and whole-school transformation – providing a European model for translating global PA policy into national action.